2011
DOI: 10.3174/ajnr.a2350
|View full text |Cite
|
Sign up to set email alerts
|

Association of Olfactory Bulb Volume and Olfactory Sulcus Depth with Olfactory Function in Patients with Parkinson Disease

Abstract: BACKGROUND AND PURPOSE:Olfactory dysfunction is commonly associated with IPD. We here report the association of OB volume and OS depth with olfactory function in patients with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 34 publications
4
112
0
Order By: Relevance
“…Although the reported prevalence of olfactory loss in PD varies across studies, it appears that as much as 50-90% of PD patients experience varying degrees of olfactory dysfunction, and that there is no correlation between the degree of olfactory dysfunction and the duration or clinical severity of the disease (Doty et al, 1988;Stern et al, 1994;Hawkes et al, 1997;Hawkes, 2003). The pathological substrate for this olfactory loss is not clear, some studies reporting conflicting information about damage to the olfactory epithelium or changes in olfactory bulb volumes as potential sources of these deficits (Muller et al, 2005;Witt et al, 2009;Wang et al, 2011). However, various studies have now reported an increase in the total number of periglomerular dopaminergic cells in the olfactory bulb of parkinsonian patients (Huisman et al, 2004;Morley and Duda, 2010).…”
Section: Early Anosmiamentioning
confidence: 84%
“…Although the reported prevalence of olfactory loss in PD varies across studies, it appears that as much as 50-90% of PD patients experience varying degrees of olfactory dysfunction, and that there is no correlation between the degree of olfactory dysfunction and the duration or clinical severity of the disease (Doty et al, 1988;Stern et al, 1994;Hawkes et al, 1997;Hawkes, 2003). The pathological substrate for this olfactory loss is not clear, some studies reporting conflicting information about damage to the olfactory epithelium or changes in olfactory bulb volumes as potential sources of these deficits (Muller et al, 2005;Witt et al, 2009;Wang et al, 2011). However, various studies have now reported an increase in the total number of periglomerular dopaminergic cells in the olfactory bulb of parkinsonian patients (Huisman et al, 2004;Morley and Duda, 2010).…”
Section: Early Anosmiamentioning
confidence: 84%
“…Age-related changes in the volume of OB have been documented in vivo using magnetic resonance imaging (MRI) [34], although such decrements are not specific to aging and may occur under several conditions, including smoking, chronic sinusitis, multiple sclerosis, head trauma, and schizophrenia [12]. Correlations were found between odour recognition thresholds and OB volumes in both PD patients (p < 0.05) and controls (p < 0.0001) [35]. Glomerular degeneration occurs in aged humans with AD, where the glomeruli express Aβ precursor protein, β-secretase, and the γ-secretase complex.…”
Section: Causes Of Age-related Loss Of Olfactionmentioning
confidence: 99%
“…In one study conducted on the sense of smell, it has been suggested that PD may be detected by the presence of anosmia together with executive dysfunctions long before motor symptoms occur (Ponsen et al 2009). Additionally, hyposmia or anosmia has been reported to be an important indicator for PD and this condition has been supported by morphological studies pointing out PD to coexist with olfactory bulbus atrophy (Wang et al 2011).…”
Section: Introductionmentioning
confidence: 86%